Mitochondrial lipids in Bufo arenarum full-grown oocytes - Gili, Valeria (2004)
Both the content and composition of polar and neutral lipids from the mitochondrial fraction of ovarian full-grown Bufo arenarum oocytes were analysed in the present study. Triacylglycerols (TAG) represent 33% of the total lipids, followed by phosphatidylcholine (PC), free fatty acids (FFA) and phosphatidylethanolamine (PE). Diphosphatidylglycerol (DPG) or cardiolipin, a specific component of the inner mitochondrial membrane, represents about 4% of the total lipid content. Palmitic (16:0) and arachidonic (20:4n6) acids are the most abundant fatty acids in PC and PE, respectively. DPG is enriched in fatty acids with carbon chain lengths of 18, the principal component being linoleic acid. In phosphatidylinositol (PI), 20:4n6 and stearic acid (18:0) represent about 72 mol% of the total acyl group level. The main fatty acids in TAG are linoleic (18:2), oleic (18:1), and palmitic acids. The fatty acid composition of FFA and diacylglycerols (DAG) is similar, 16:0 being the most abundant acyl group. PE is the most unsaturated lipid and sphingomyelin (SM) has the lowest unsaturation index.